Connecting dots in disorders of gut-brain interaction: the interplay of stress and sex hormones in shaping visceral pain - Labrenz, Franziska; Merz, Christian J.; Icenhour, Adriane (Frontiers in Psychiatry, 2023)
Visceral pain and stress are tightly intertwined bodily and emotional phenomena, which enable a flexible adaptation to environmental challenges by activating a response repertoire to restore homeostasis along the gut-brain axis. However, visceral pain and stress can persist widely independent of the initial cause, acquiring independent disease values and posing major health burdens as predominant features in disorders of gut-brain interaction (DGBI). Epidemiological data consistently documents an increased prevalence for women to suffer from chronic visceral pain, possibly shaped by sex hormones and modulated by stress and its biological and psychosocial correlates. Yet, mechanisms underlying the complex interactions between altered visceroception, stress and sex remain widely elusive, especially in clinical populations with DGBI. We herein selectively review mechanisms of interactions between stress and sex in the complex pathophysiology of DGBI. A particular emphasis is laid on visceral pain, in which stress constitutes a major risk factor as well as mediator, and sex-related differences are particularly pronounced. Building on the neurobiology of stress and mechanisms of gut-brain interactions, we highlight putative target mechanisms via which visceral pain and stress may converge with sex effects into a triad. Accommodating a global demographic shift, we propose a lifespan perspective in future research, which may enable a more fine-tuned evaluation of this complex interplay exerting distinct challenges during vulnerable developmental phases. This viewpoint may advance our understanding of pathophysiological processes and can ultimately inspire novel tailored prevention strategies and therapeutic approaches in the treatment of chronic visceral pain and DGBI across the lifespan.